GREEN SYNTHESIS OF TIO2 USING ALOE VERA FOR PHOTODEGRADATION IN SASIRANGAN WASTE - Asyiah, Noor; Ahmad, Ahmad; Ananda, Tarisa; Muhaemina, Maulanie; Rosadi, Jannesa Tri; Suryajaya, Suryajaya; Safitri, Maya (Universitas Mataram, 2025)
Green synthesis of TiO2 has been successfully carried out using aloe vera. Aloe vera extract was mixed with TiCl4 while heated to obtain TiO2 powder. The FTIR spectrum showed a peak at 487.67 cm-Â¹ corresponding to the Ti-O-Ti functional group, which indicates the formation of TiO2 particles. The XRD results showed that the TiO2 crystals were in the anatase phase. SEM images show that the particles tend to be spherical in shape as in the anatase phase. With the Scherer equation, the size of the TiO2 crystal yielded was around 2.3 nm in diameter. The UV-vis spectrophotometer results showed the blue shift of absorption peak at 368 nm or band gap energy of 3.37 eV. A thin layer of TiO2 was made by using the slip casting method. These thin films were applied to methylene blue and sasirangan waste samples for photodegradation tests. The exposure times used were 15, 30, 45, 60, and 75 minutes. The results showed photodegradation of 38.9 % and 4.5 %, respectively, for methylene blue and sasirangan waste.